A Burning Question: What are the Implications of Forest Fires for Woodland Caribou?. Issue 8 (16th August 2021) - Konkolics, Sean; Dickie, Melanie; Serrouya, Robert; Hervieux, Dave; Boutin, Stan
ABSTRACT: Canada's federal recovery strategy for boreal woodland caribou ( Rangifer tarandus caribou ) classifies areas burned by forest fire as disturbed habitat. This assignment of fire as a disturbance has potential economic and social implications across Canada, and influences plans and actions to achieve caribou conservation and recovery. Previous researchers have reported caribou avoid burned habitat, but these studies did not typically consider unburned residual patches within fire perimeters. Additionally, the implications of burned habitat on individual caribou survival is unclear. We examined resource selection by boreal woodland caribou of burns, and unburned residual patches, using global positioning system (GPS) locations for 201 caribou across 6 caribou populations in Alberta, Canada. We also examined if burned habitat affected the survival of adult female caribou. Caribou avoided burns and unburned residual patches. Increased use of burned habitats, however, did not lower the survival of adult caribou. Collectively, these results provide evidence to support current assertions that burns, and the embedded unburned residual patches are not preferred caribou habitat and increase our understanding of the implications of forest fire for caribou vital rates. Our investigation offers important information about the role of forest fire in caribou ecology and enhances the identification of disturbed habitat under recovery strategy guidelines to effectively address caribou population declines. © 2021 The Wildlife Society.  : Woodland caribou in Alberta, Canada avoid burned habitat including unburned residual patches; however, there was no relationship between burned habitat use and adult female survival. This suggests fire disturbance is not a key influence of caribou population persistence, and we recommend reevaluation of the current approach listed in the federal boreal caribou recovery strategy that includes anthropogenic and fire disturbance in a cumulative assessment of disturbed habitat.